Population structure and flowering and fruiting characteristics of the endangered tree, Padus avium var. avium, in the Tohoku region - Nakabayashi, Ayaka; Kurauchi, Yui; Ishida, Kiyoshi (Tohoku Journal of Forest Science, 2021)
We studied the population structure and flowering and fruiting characteristics of two populations of the endangered tree Padus avium var. avium, in Goshogawara and Itayanagi, Aomori Prefecture, Tohoku region. The two populations comprised 151 stands with the stem girth at breast height of 15 cm or higher, which were distributed across 15 patches. The number and local density of the patches were lower in Goshogawara than in Itayanagi. The patches in Itayanagi were estimated to bear 20 % more hermaphrodite flowers than the patches of the same size in Goshogawara. Furthermore, the fruit set of the two populations was rather low (0.9 %). Fruit set per patch significantly differed between the two populations, and the weighted means of fruit set using patch size as the weight also indicated substantial differences in the fruit set between the two populations. In Itayanagi, patches with larger stems tended to exhibit higher fruit set. In pollination experiments, the species exhibited partial self-incompatibility and the pollen limitation index of the two populations was 0.98–0.99, suggesting that limited cross-pollination results in a low fruit set. Also, cross-pollinated flowers achieved a relatively low fruit set (17 %), suggesting that factors other than limited cross-pollination are associated with the fruit set. Further studies elucidating the causes of low fruit set are essential for the effective conservation management of P. avium var. avium, in the Tohoku region.